Changes in Volatile Compounds of Dark and Ordinary Muscles of Yellowtail (Seriola quinqueradiata) During Short-Term Cold Storage. Issue 2 (17th February 2016) - Tanimoto, Shota; Shimoda, Mitsuya
ABSTRACT: Changes in volatile compounds in dark and ordinary muscle of yellowtail during 2 days of refrigerated storage at 5°C were investigated. Twenty-seven compounds were identified in ordinary muscle and 39 in dark muscle during 2 days of storage at 5°C. Thirteen compounds at Day 0 of storage and 29 compounds at Day 2—such as 2, 3-pentadione, 1-penten-3-ol, (Z)-2-penten-1-ol, and (E, Z)-2, 4-heptadienal—identified in the dark muscle showed significantly higher values compared to ordinary muscle. Levels of thiobarbituric acid-reactive substances (TBARS) in dark muscle were significantly higher than those in ordinary muscle throughout 2 days of storage period, and a significant increase in TBARS occurred in just dark muscle at Day 2 of storage. In ordinary muscle, viable cells remained at the same order of magnitude as their initial values for 2 days. Eight aldehydes in ordinary muscle and 25 volatile compounds in dark muscle increased significantly without microbial action prior to increase in TBARS during short-term cold storage. Principal component analysis of the volatile compounds in dark and ordinary muscle was able to differentiate between different storage time samples of same muscle type as well as different muscle samples of same storage time.